The influence of gender, media, and internet usage on adolescents' fast food perception and fluid intake - Ahmad R. Al-Haifi; Nayef Y. Bumaryoum; Balqees A. Al-Awadhi; Fahad A. Alammar; Rasha H. Ashkanani; Hazzaa M. Al-Hazzaa (BMC, 2023)
Abstract Background Understanding the factors that influence adolescent's perception of fast food and their fluid consumption is crucial for designing effective nutrition education programs tailored to this population. This study aimed to evaluate the associations of sex and the use of media and the internet with adolescents' perception of fast foods and the amount of fluid consumption. Methods A cross-sectional survey was conducted on school adolescents between the ages of 15 and 18 years in Kuwait, using a multistage stratified random sampling method (N = 706 adolescents; 343 boys and 363 girls). A pre-tested and specifically designed self-report questionnaire covering several measures such as: (a) types of foods that are considered fast foods; and (b) participant's fluid consumption. Body weight and height were measured using calibrated medical scales. Body mass index (BMI) was computed. The adolescents were stratified by sex into two groups: boys and girls, for the purpose of analysis. Results Seven out of 14 food choices showed significant sex differences (p values ranged from 0.016 to < 0.001) in the adolescents' responses to whether they perceived such food choice as fast food or not. Although differences were found between sexes, the majority of the listed fast foods were correctly recognized as fast foods by the adolescents. In addition, there were significant differences between males and females in the amount of daily drinks (ml/week) consumed from full fat milk (males = l197.1 ± 27,652.1 and females = 1662.8 ± 2221, p = 0.013), sugar-sweetened beverage (males = 2350.8 ± 3324.3 and females = 3088.9 ± 3701.1, p = 0.004), and energy drinks (males = 429.5 ± 1117.2 and females = 267.6 ± 733.8, p = 0.037). Compared to adolescents who seldom or do not watch TV or use the internet, those who engage in these sedentary activities are less likely to classify pizza (aOR (95% CI) = 0.660 (0.440-0.990), p = 0.045), grilled meat (aOR (95% CI) = 0.674 (0.477-0.954), p = 0.026), fried egg sandwiches (aOR (95% CI) = 0.617 (0.425-0.894-0.189), p = 0.011), and rice (aOR (95% CI) = 0.598(0.409-0.875), p = 0.008) as fast foods. Conclusion The influence of TV and internet use on adolescent's ability to accurately identify fast foods has been observed. Findings indicate the need for increased fast food nutrition education programs that are tailored towards adolescents. The study recommends further research to enhance consumer awareness of foods and drinks among adolescents in the State of Kuwait.